Palladium‐Catalyzed 3‐Aryl‐5‐acyl‐1, 2, 4‐thiadiazole Formation from Ketones, Amidines, and Sulfur Powder. Issue 12 (27th March 2017) - Wang, Zilong; Xie, Hao; Xiao, Fuhong; Guo, Yanjun; Huang, Huawen; Deng, Guo‐Jun
Abstract : An efficient strategy for the preparation of 3, 5‐disubstituted 1, 2, 4‐thiadiazoles from ketones, amidines, and sulfur powder under palladium‐catalyzed conditions was developed. In this transformation, aromatic ketones act as both the carbon and acyl sources. The reaction provided efficient access to 3‐aryl‐5‐acyl‐1, 2, 4‐thiadiazoles from readily available starting materials. Abstract : An efficient strategy to prepare 3, 5‐disubstituted 1, 2, 4‐thiadiazoles from ketones, amidines, and sulfur powder under palladium‐catalyzed conditions is developed. Aromatic ketones act as the carbon and acyl sources in this transformation. This reaction provides efficient access to 3‐aryl‐5‐acyl‐1, 2, 4‐thiadiazoles from readily available starting materials.